THE CONTRIBUTION OF THE CHARACTER VALUES OF THE GANDAVYUHA SUTRA TO THE PROFILE OF PANCASILA STUDENTS - Kristanto, Bara Andhi; Sukodoyo; Kustiani, Kustiani; Suranto, Suranto (Syailendra Buddhist College / Sekolah Tinggi Agama Buddha (STAB) Syailendra, 2024)
The background of this research is the fading of Pancasila character values in Indonesian students, causing various problems. The lack of character values related to students in Buddhism, especially in the Gandavyuha Sutra. The purpose of this study was to determine the relationship and contribution of the Gandavyuha Sutra to the profile of Pancasila students in the world of education. This study uses the literature study method (synthesise checklist), which consists of preliminary, advanced, and final syntheses, taking into account the elements of text, context, and discourse. The analysis component of this study includes elements of text, context, and discourse. The interrelatedness of these three components forms a single entity that contributes the character values of the Gandavyuha Sutra to the Pancasila Student Profile. The results of this study are that the Pancasila Student Profile is a programme created by the government to shape student character with the spirit of Pancasila. There are character values in the Gandavyuha Sutra that are related to the Pancasila Student Profile, including the values of faith, tolerance, interaction and social care, social solidarity, compassion, help, self-motivation, strong determination, enthusiasm, wisdom, and creativity. These interrelated character values also contribute in terms of traits, attitudes, and actions so that they can be applied to school learning activities such as projects to strengthen the Pancasila Student Profile. These activities include extracurricular activities, teaching and learning activities, school routine activities, and other school environment activities.